Learning the post-Fordist feeling rules: Young women's work orientations and negotiations of the work ethic - Lamberg Emma (SAGE PUBLICATIONS LTD, 2022)
Even though flexibility, insecurity and precarity characterise much of today’s work, the promise of self-realisation through work remains as powerful as ever. Following Weeks’ work on the post-Fordist work ethic and Hochschild’s research on feeling rules, this article analyses how young women negotiate the post-Fordist work ethic and its emotional obligations. Drawing on interviews with 39 young women studying in the care and media fields in Finland, the article proposes the conceptualisation of post-Fordist feeling rules as a way to capture how young women become workers by managing contemporary work’s emotional requirements and contradictions. This article adds to the sociology of youth and labour in the post-Fordist era by foregrounding the role of feelings in the production of youth as workers and unpacking the post-Fordist work ethic’s gendered, industry-specific and emotional dimensions.